Spreading of Dangerous Skin-Lightening Products as a Result of Colourism: A Review - Claudia C. A. Juliano (Applied Sciences, 2022)
The use of bleaching products can have a medical or cosmetic purpose; in the latter case, skin whitening is most widespread in countries where darker skin tones prevail and can be driven by psychosocial, cultural and economic reasons. Skin-whitening products containing highly toxic active ingredients (in particular mercury derivatives, hydroquinone and corticosteroids) are easily found on the market; the use of these depigmenting agents can be followed by a variety of adverse effects, with very serious and sometimes fatal complications, and is currently an emerging health concern in many countries. This article concisely discusses the reasons for the current prevalence of skin lightening products and provides an overview of the skin lightening agents that pose a threat to human health. The review also reports market surveillance data on the circulation of banned skin lighteners in Europe, obtained through the Safety Gate system.